Evaluation of the Work Safety and Psychosocial Wellbeing of Disability Support Workers. (20th October 2015) - Harries, Julia; Ng, Ka Yiu Yoyo; Wilson, Leah; Kirby, Neil; Ford, Jerry
Abstract : This study investigated organisational factors impacting disability support worker (DSW) psychosocial wellbeing and work safety to understand the relationship between wellbeing, using measures of burnout and job satisfaction, and work conditions and safety performance. This study also investigated factors predicting wellbeing using the Job Demand-Control-Support (JDCS) model. A sample of 87 DSWs completed normed measures of burnout, work conditions, and safety climate. Results showed DSWs experienced significantly higher personal and work-related burnout but significantly lower client-related burnout. Although the JDCS model components did not all predict any single wellbeing measure, they each predicted aspects of burnout and job satisfaction, with these wellbeing measures associated with safety performance. Findings highlighted the importance of monitoring worker job demands, support availability, and job control to improve safety performance. Compared to normative data, DSWs were experiencing significantly higher role conflict, the negative impact of which was effectively moderated by support for personal and work-related burnout and job satisfaction. Findings suggest the need to consider DSW work conditions, and particularly work practices contributing to role conflict, as well as increasing support for DSWs to prevent the development of personal and work-related burnout. Findings suggest further research associated with client-related burnout is required.